2000
DOI: 10.1098/rspb.2000.1173
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime success and interactions of farm salmon invading a native population

Abstract: Farm Atlantic salmon escape and invade rivers throughout the North Atlantic annually, which has generated growing concern about their impacts on native salmon populations. A large-scale experiment was therefore undertaken in order to quantify the lifetime success and interactions of farm salmon invading a Norwegian river. Sexually mature farm and native salmon were genetically screened, radio tagged and released into the River Imsa where no other salmon had been allowed to ascend. The farm ¢shes were competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
576
6
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(623 citation statements)
references
References 39 publications
36
576
6
5
Order By: Relevance
“…We predict that, in situations where there are few or no predators, significant numbers of domestic survivors will survive, compete and hybridize with wild fish. Wild stocks are likely to dwindle in this scenario (Muir & Howard 1999), owing to the low fitness of hybrids (Fleming et al 2000;McGinnity et al 2003). When predators are common, however, few domestic fish will survive and then compete and mate with wild fish, their progeny will also have high mortality, and invasion will be less likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We predict that, in situations where there are few or no predators, significant numbers of domestic survivors will survive, compete and hybridize with wild fish. Wild stocks are likely to dwindle in this scenario (Muir & Howard 1999), owing to the low fitness of hybrids (Fleming et al 2000;McGinnity et al 2003). When predators are common, however, few domestic fish will survive and then compete and mate with wild fish, their progeny will also have high mortality, and invasion will be less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Each year, tens of thousands of domestic salmonids escape into the Pacific and Atlantic oceans from netcage aquaculture operations, and potentially threaten wild populations (Gross 1998). Field studies have been undertaken of the reproductive behaviour and success of escapees and their hybrids (Fleming et al 2000;McGinnity et al 2003), and laboratory studies show a greater willingness of domestic fishes to accept risk to access food-rich habitats (e.g. Johnsson & Abrahams 1991;Johnsson et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Natural selection against domesticated fish and their descendants is generally assumed to be strong and may involve juvenile survival (McGinnity et al 2003), marine survival and return rate (McGinnity et al 2003;Ruzzante et al 2004) and spawning competition (Fleming et al 2000). However, in the case of the Skjern River selection against domesticated trout has not overcome the rate of 'immigration' because of stocking, as evidenced by the high and permanent admixture proportions of domesticated trout.…”
Section:    mentioning
confidence: 99%
“…It has been shown that overexploitation in fisheries can induce a rapid loss of genetic variation of target species, which may diminish the adaptability and persistence of the species (Hauser et al 2002;Hutchinson et al 2003;Smith et al 1991;Turner et al 2002). A lack of a policy regarding farming industries can result in introgression of non-native or domesticated genes into wild populations, potentially causing a loss in genetic variability (Bekkevold et al 2006;Fleming et al 2000;Hindar et al 2006;McGinnity et al 2003). Investigating genetic diversity and population structure of species, after overexploitation and/or introgression have occurred, fails to maximize the potential for using this knowledge as a tool to aid in the development of policy which adequately protects biodiversity in the wild populations from anthropogenic influences.…”
Section: Introductionmentioning
confidence: 99%